Modeling travel decisions: Urban exploration, cultural immersion, or both?. Issue 3 (24th March 2017) - Falk, Martin; Katz-Gerro, Tally
ABSTRACT: This paper investigates the characteristics of the choice between cities and culture (or aspects of both) in selecting certain travel destinations. The data consist of 28, 700 individuals in 32 European countries. Bivariate probit model estimates show that those with moderately and skilled occupations, students, pensioners, women, people living in cities and regions with a high gross domestic product per capita have a higher joint probability of undertaking city and cultural trips. Furthermore, there are large differences in decisions to take a combined city and cultural trip across the countries of residence surveyed, with small western European countries exhibiting the highest probability.